Influence of functional health literacy on adherence to antidepressant treatment - Alessandro Magon de Sá; Vanessa Casagrande; Eduardo Federighi Baisi Chagas; Osni Lázaro Pinheiro (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To verify the influence of patients' level of functional health literacy on adherence to antidepressant treatment. Method Cross-sectional study, carried out in pharmacies of the Municipal Health Department of Marília-SP, in 2020/2021. The functional literacy questionnaire verified the numerical and interpretative skills of patients, in the face of texts related to the health area. The adherence to the treatment was verified using the Morisky therapeutic adherence scale, and the data were analyzed by Anova-one-way and Kruskal-Wallis tests. Results A total of 150 patients participated in the study, most of them showed failures in adherence and an inadequate level of functional health literacy. However, there was no correlation between functional health literacy and treatment adherence. Conclusion Although no correlation was found between the variables, there is a need for greater investments in terms of adherence to the treatment, with strategies that consider the level of functional health literacy in these patients.